Lateral reticular nucleus modulates the cardiosomatic reflex evoked by intrapericardial capsaicin in the rat. Issue 9 (7th March 2013) - Han, Man; Liu, Xiao‐Hua; Sun, Na; Du, Jian‐Qing; Zhu, Juan‐Xia; Li, Qiang; Tang, Jing‐Shi
Abstract The current study examined the role of the lateral reticular nucleus (LRN) in modulating the cardiosomatic reflex (CSR) induced by intrapericardial capsaicin in the anesthetized rat. Intrapericardial capsaicin was administered, and the CSR was monitored via electromyogram responses of the dorsal spinotrapezius muscle. Electrical stimulation of the LRN (10, 20 and 30 μA) depressed the CSR induced by intrapericardial capsaicin in an intensity‐dependent manner. Microinjection of glutamate (4, 10, 20 and 40 nmol, in 0.2 μL) into the LRN replicated the effects of electrical stimulation. Furthermore, bilateral transections of the dorsolateral funiculus (DLF) decreased the LRN electrical stimulation‐induced inhibition of the electromyogram responses. Intrathecal administration of the α2‐adrenergic receptor antagonist yohimbine or the serotonergic receptor antagonist methysergide significantly attenuated the LRN electrical stimulation‐induced inhibition of the electromyogram responses. However, intrathecal application of the opioid receptor antagonist naloxone had no effect on the LRN electrical stimulation‐induced inhibition. These results suggest that the LRN–DLF–spinal cord pathway is involved in descending inhibition of the CSR, and spinal α2‐adrenergic and serotonergic receptors participate in this descending inhibition.